L’histoire urbaine à l’épreuve des plaintes citadines (xviie-xxe siècles) : introduction - Isabelle Backouche; Nathalie Montel (L'Atelier du CRH)
What if ordinary city-dwellers ’voices were taken into account earnestly? This is the issue’s premise, which focuses on a corpus of written complaints where the city is both setting and motive. What do these low-key protests convey? To what extent do they inform us regarding the making of the city? These out-of-the-ordinary sources provide historians with invaluable novel insights into the social and material transformations of urban environments. This is what each of the papers gathered here endeavour to expose